The Role of Job Crafting and Job Embeddedness Mediation on Intention To Stay In Health Workers - Farid, Ridhayati; Sitorus, Silvia Monica; Asri, Dhita Hafizha (Jurnal Ekuilnomi, 2026)
This research aims to analyze the effect of social support and organizational support on the intention to stay of healthcare workers, mediated by job crafting and job embeddedness. The background of this research stems from the high turnover rate of healthcare workers in Indonesia. This is a quantitative research with a cross-sectional design through the distribution of questionnaires to 363 healthcare workers in Batam City. The data were analyzed using PLS-SEM. The results showed that social support affects job crafting and job embeddedness but does not directly affect intention to stay. Otherwise, organizational support significantly affects intention to stay both directly and indirectly through job embeddedness. Job crafting mediation is only significant in the relationship between social support and intention to stay, while job embeddedness mediation is more dominant in the relationship between organizational support and intention to stay